A healthcare utilization cost comparison between employees receiving a worksite mindfulness or a diet/exercise lifestyle intervention to matched controls 5 years post intervention. (August 2016) - Klatt, Maryanna D.; Sieck, Cynthia; Gascon, Gregg; Malarkey, William; Huerta, Timothy
Highlights: A retrospective economic evaluation of worksite CAM interventions was conducted. A propensity matched score generated a viable control group on salient variables. Pharmaceutical cost and use by intervention groups was higher than controls. CAM interventions generated overall cost savings over 5 years compared to controls. Abstract: Objective: To compare healthcare costs and utilization among participants in a study of two active lifestyle interventions implemented in the workplace and designed to foster awareness of and attention to health with a propensity score matched control group. Design and setting: We retrospectively compared changes in healthcare (HC) utilization among participants in the mindfulness intervention (n = 84) and the diet/exercise intervention (n = 86) to a retrospectively matched control group (n = 258) drawn for this study. The control group was matched from the non-participant population on age, gender, relative risk score, and HC expenditures in the 9 month preceding the study. Main outcome measures: Measures included number of primary care visits, number and cost of pharmacy prescriptions, number of hospital admissions, and overall healthcare costs tracked for 5 years after the intervention. Results: Significantly fewer primary care visits (p < .001) for both intervention groups as compared to controls, with a non-significant trend towards lower overall HC utilization (4, 300.00 actual dollar differences) and hospital admissions for the intervention groups after five years. Pharmacy costs and number of prescriptions were significantly higher for the two intervention groups compared to controls over the five years (p < 0.05), yet still resulted in less HC utilization costs, potentially indicating greater self-management of care. Conclusion: This study provides valuable information as to the cost savings and value of providing workplace lifestyle interventions that focus on awareness of one's body and health. Health economic studies validate the scale of personal and organization health cost savings that such programs can generate.